Hymenaea stigonocarpa Mart. ex Hayne: A Brazilian medicinal plant with gastric and duodenal anti-ulcer and antidiarrheal effects in experimental rodent models - Orsi, Patricia Rodrigues [UNESP]; Bonamin, Flavia [UNESP]; Severi, Juliana Aparecida [UNESP]; Santos, Raquel Cassia [UNESP]; Vilegas, Wagner [UNESP]; Hiruma-Lima, Clélia Akiko [UNESP]; Di Stasi, Luiz Claudio [UNESP] (Elsevier B.V., 2012)
Ethnopharmacological relevance: Hymenaea stigonocarpa Mart. ex Hayne (Fabaceae) is a medicinal species commonly found in the Brazilian savannah. The stem bark of this medicinal plant, popularly known as jatoba-do-cerrado, is widely used in tea form to treat gastric pain, ulcers, diarrhoea and inflammation, whereas its fruits pulp is edible.Aim of the study: The aim of this study was to investigate the antidiarrheal and anti-ulcer effects of a methanolic extract derived from the stem bark (MHs) and diet with fruit pulp of H. stigonocarpa.Materials and methods: The antidiarrheal action of MHs was measured against the intestinal motility and diarrhoea induced by castor oil in mice. The preventive action of MHs (50, 100, 150 and 200 mg/Kg, by oral route (p.o.)) against peptic ulcers was evaluated in experimental rodent models challenged with absolute ethanol, non-steroidal anti-inflammatory drugs (NSAIDs), ischemia-reperfusion (I/R) (200 mg/Kg, p.o.) and cysteamine (200 mg/Kg, p.o.). The main anti-ulcer mechanisms of action of MHs were analysed as follows: evaluation of the gastric juice parameters, assessment of mucus adherence to the gastric wall, determination of the role of nitric oxide (NO) and sulfhydryl compounds (SH), glutathione (GSH) levels and myeloperoxidase (MPO) activity. The healing effects from MHs (200 mg/Kg) and diet with fruit pulp (10%) against gastric and duodenal ulcers induced by acetic acid were also evaluated by treating rats over 7 or 14 consecutive days of treatment.Results: The phytochemical profile of MHs and fruit pulp indicated the presence of phenolic compounds (mainly flavonoids and condensed tannins). MHs (200 mg/Kg, p.o.) displayed an antidiarrheal effect and were able to protect gastric mucosa against absolute ethanol (68% protection) and also against the injurious effect of NSAIDs (86% protection) when compared to the group treated with vehicle. These results were accompanied by the prevention of GSH depletion and an inhibition of MPO activity when compared to animals treated with vehicle (P < 0.05). MHs markedly protected duodenal mucosa against injuries caused by cysteamine (98%) and also against I/R induced gastric ulceration (80%) when compared to the group treated with vehicle. Furthermore, MHs also prevented the GSH depletion of gastric mucosa relative to the control group treated with vehicle. NO appeared to be involved in this gastroprotective effect. MHs and diet with fruit pulp clearly demonstrated gastric healing actions after treatment for 7 (MHs - 53% inhibition) or 14 days (MHs - 60% inhibition and fruit pulp - 61% inhibition). Treatment with diet with fruit pulp for 7 days demonstrates a significant duodenal healing effect (71% inhibition) without any signs of toxicity.Conclusions: MHs clearly demonstrate antidiarrheal, gastroprotective and cicatrising effects in experimental gastric and duodenal ulcers, and the diet with fruit pulp displays duodenal healing effects. The observed effects may be associated with the antioxidant effect, which may be due the presence of condensed tannins and flavonoids in the bark and fruit of H. stigonocarpa. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Hymenaea stigonocarpa; Fabaceae; Peptic ulcer; Tannins; Antidiarrheal; Antioxidant